Liver stiffness by transient elastography predicts liver-related complications and mortality in patients with chronic liver disease. - Jack X Q Pang; Scott Zimmer; Sophia Niu; Pam Crotty; Jenna Tracey; Faruq Pradhan; Abdel Aziz M Shaheen; Carla S Coffin; Steven J Heitman; Gilaad G Kaplan; Mark G Swain; Robert P Myers (PLoS ONE, 2014)
Liver stiffness measurement (LSM) by transient elastography (TE, FibroScan) is a validated method for noninvasively staging liver fibrosis. Most hepatic complications occur in patients with advanced fibrosis. Our objective was to determine the ability of LSM by TE to predict hepatic complications and mortality in a large cohort of patients with chronic liver disease.In consecutive adults who underwent LSM by TE between July 2008 and June 2011, we used Cox regression to determine the independent association between liver stiffness and death or hepatic complications (decompensation, hepatocellular carcinoma, and liver transplantation). The performance of LSM to predict complications was determined using the c-statistic.Among 2,052 patients (median age 51 years, 65% with hepatitis B or C), 87 patients (4.2%) died or developed a hepatic complication during a median follow-up period of 15.6 months (interquartile range, 11.0-23.5 months). Patients with complications had higher median liver stiffness than those without complications (13.5 vs. 6.0 kPa; P<0.00005). The 2-year incidence rates of death or hepatic complications were 2.6%, 9%, 19%, and 34% in patients with liver stiffness <10, 10-19.9, 20-39.9, and ≥40 kPa, respectively (P<0.00005). After adjustment for potential confounders, liver stiffness by TE was an independent predictor of complications (hazard ratio [HR] 1.05 per kPa; 95% confidence interval [CI] 1.03-1.06). The c-statistic of liver-stiffness for predicting complications was 0.80 (95% CI 0.75-0.85). A liver stiffness below 20 kPa effectively excluded complications (specificity 93%, negative predictive value 97%); however, the positive predictive value of higher results was sub-optimal (20%).Liver stiffness by TE accurately predicts the risk of death or hepatic complications in patients with chronic liver disease. TE may facilitate the estimation of prognosis and guide management of these patients.